2001
DOI: 10.1093/aje/153.9.898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination Therapy on Immunologic Progression of Human Immunodeficiency Virus at a Population Level

Abstract: There is accumulating evidence from clinical trials and cohort studies that highly active antiretroviral combination therapy is effective at halting immunologic and clinical progression of human immunodeficiency virus (HIV). Its impact at a population level is less well known because the regimes may be difficult to tolerate and compliance poorer. The authors make use of population data for almost all of the HIV-infected people in Scotland in 1997 who were under clinical care and monitor their response to thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Studies of the effect on all HIV-diagnosed persons have not been found in the literature. The study closest to being a study of all HIV-diagnosed persons has been carried out in Scotland (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the effect on all HIV-diagnosed persons have not been found in the literature. The study closest to being a study of all HIV-diagnosed persons has been carried out in Scotland (7).…”
Section: Introductionmentioning
confidence: 99%
“…The lesser effect on progression to AIDS for HIVdiagnosed IDUs is also found in Scotland. In a study by Parpia et al of 95% of patients in medical care for HIV in Scotland, IDUs were less frequently on effective triple/quadruple treatment (6% vs 15% among men infected through sex with men and 10% among persons infected heterosexually) (7). IDUs more frequently had no treatment (35% vs 18% among men infected through sex with men and 32% among persons infected heterosexually).…”
mentioning
confidence: 99%
“…An annual Survey of Prevalent HIV Infections Diagnosed (SOPHID) was introduced in England, Wales and Northern Ireland in 1995 to monitor the number of people accessing treatment and care through the (national) health service [68]. In Scotland, equivalent information is collected through a surveillance system involving the collection of CD4 count data [69]. Improvements in survival and continued diagnoses among gay men have led to increasing numbers living with diagnosed HIV ; 17 932 gay men were accessing services in 2004 compared with 11 846 in 2000 ( Fig.…”
Section: Gay Men Living With Diagnosed Hiv Infection: 1996 Onwardsmentioning
confidence: 99%
“…The current standard combination antiretroviral therapy (cART) for HIV-1 infection restores the immune function by limiting the progression of the disease [ 1 ]. The introduction of cART in clinical practice significantly reduced HIV-related morbidity and mortality, improving the quality of life (QoL) of people infected with HIV [ 2 ].…”
Section: Introductionmentioning
confidence: 99%